Epidemiology and Genetic Variabilities of Human Adenovirus Type 55 Reveal Relative Genome Stability Across Time and Geographic Space in China - Chen, Shi-ying; Liu, Wenkuan; Xu, Yun; Qiu, Shuyan; Chen, Yong; Tian, Xingui; Zhou, Rong (Frontiers in Microbiology, 2020)
After the first outbreak in China in 2006, human adenovirus type 55 (HAdV-B55) has become a common pathogen causing life threatening pneumonia in northern China. However, HAdV-B55 infection has been rarely reported in southern China. Here, we collected throat swabs from 3192 hospitalized children with acute respiratory disease (ARD) from May 2017 to April 2019 in Guangzhou, southern China, tested them for HAdV-B55 infection. Only one of 1399 patients from May 2017 to April 2018 was HAdV-B55 positive; HAdV-B55 infections significantly increased with 10 of 1792 patients testing positive since May 2018. HAdV-B55-267, isolated from a case of death, was sequenced for whole genomic analysis. Three other strains, HAdV-B55-Y16, -TY12, and -TY26, isolated earlier in patients from Shanxi, northern China, were also sequenced and analyzed. The four HAdV-B55 strains formed similar plaques, grew to similar titers, and resulted in similar typical cell pathogenic effects. HAdV-B55-267 formed a subclade with the prototype strain QS-DLL; strains HAdV-B55-Y16, -TY12, and -TY26 were closely related to strain QZ01. HAdV-B55 could be divided into two subtypes (HAdV-B55-a and -b) according to the presence or absence of the insertion of “CCATATCCGTGTT”; all strains isolated from China except for strain BJ01 belong to subtype b. HAdV-B55-267 had only one non-synonymous substitution comparing with strain QS-DLL, and all HAdV-B55 strains had highly conserved capsid proteins and few non-synonymous substitutions. This study suggests that HAdV-B55 is an important pathogen associated with ARD in Guangzhou since 2018, exhibiting the relative genome stability across time and geographic space in China.